DATING CRYSTALLINE GROUNDMASS SEPARATES OF ALTERED CRETACEOUS SEAMOUNT BASALTS BY THE 40AR/39AR INCREMENTAL HEATING TECHNIQUE - Koppers A.A.P.; Staudigel H.; Wijbrans J.R. (My University, 2000)
Alteration of submarine basalts compromises geochronology using conventional K/Ar and 40Ar/39Ar techniques. To help overcome these problems, we re-evaluated the potential of groundmass dating techniques. Incremental heating on acid-leached groundmass samples, following an overnight bakeout at 200°C and using high-resolution heating schedules, eliminated most of the low temperature alteration effects in the submarine basalts studied. More than 75% of the groundmass analyses (n=32) display accurate age plateaus consisting of 30-70% of the total amount of 39ArK released. More than 50% of the analyses have plateau ages concordant with their total fusion ages implying minor or proportional loss of radiogenic 40Ar* and 39ArK. Overall, we could show a high degree of coherence between ages of groundmass separates and comagmatic phenocrysts. This suggests that the dating of aphyric basalts, which previously has proven problematic, can be accomplished with increasing confidence as well. Adding these rock types to the list of datable submarine basalts significantly enhances our ability to understand the eruptive history of linear submarine volcanic chains.
Keywords: 40AR/39AR GEOCHRONOLOGY; SEAMOUNT BASALTS; GROUNDMASS; INCREMENTAL HEATING; SEAWATER ALTERATION; RECOIL